Reducing racial/ethnic disparities in reproductive and perinatal outcomes the evidence from population-based interventions - Handler, Arden; Kennelly, Joan; Peacock, Nadine Ruth (Springer, 2011)
Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes: The Evidence from Population-Based Interventions Arden Handler, Joan Kennelly, Nadine Peacock, editors Among women?s health concerns, reproductive issues, both prenatal and postpartum, hold particular prominence. Yet despite the many programs dedicated to improving women?s reproductive health, maternal and infant morbidity and mortality rates in minority communities remain unchanged?or have increased. Confronting this alarming statistic head-on, Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes is the first book systematically examining public health interventions designed toward meeting this important and elusive goal. Its contributors offer the best thinking and practice on this complicated topic, clarifying the relationship between evidence-based medicine and evidence-based public health and its potential for increasing parity, considering interventions in the multiple contexts of women?s lives, reviewing the evidence base for each program or initiative featured, and describing methodologies for evaluating interventions. The resulting volume advocates for an integrative lifespan approach, including topics related to: Family planning STI and HIV/AIDS screening and treatment Smoking cessation and reducing exposure to environmental smoke Preconceptional well-woman care Depression screening and treatment Labor/delivery approaches and intrapartum care Emerging prenatal care interventions, from centering pregnancy to doula support For professionals and graduate students in psychiatry, psychology, sociology, women?s health, and public health, Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes reframes a set of ongoing issues and guides the reader toward state-of-the-art solutions.